2024
DOI: 10.3126/spectrum.v2i1.64771
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Determinants of Employee Turnover in the Academic Institutions of Kathmandu Valley

Asmita Khadayat,
Devid Kumar Basyal,
Purnima Lawaju
et al.

Abstract: The purpose of the study is to identify factors influencing employee turnover intention in the academic sector in Kathmandu valley. Explanatory research design is used as the main research paradigm to discover reality. It has used a purposive sampling technique where a total of 404 were interviewed with a structural questionnaire; where data collection is done by using the KOBO Toolbox. The data was evaluated by using both descriptive and inferential statistics. Structural Equation Modeling was used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Factors such as supervisor relationships, work conditions, and recognition significantly impact job satisfaction, which in turn influences turnover intentions. A study in Kathmandu Valley's academic institutions revealed that addressing challenges in salary, recognition, work-life balance, and career growth can enhance job satisfaction and reduce turnover (Khadayat et al, 2024). This emphasizes the need for comprehensive retention strategies that consider both intrinsic and extrinsic motivators.…”
Section: Introduction Importance Of Predicting Employee Turnovermentioning
confidence: 99%
“…Factors such as supervisor relationships, work conditions, and recognition significantly impact job satisfaction, which in turn influences turnover intentions. A study in Kathmandu Valley's academic institutions revealed that addressing challenges in salary, recognition, work-life balance, and career growth can enhance job satisfaction and reduce turnover (Khadayat et al, 2024). This emphasizes the need for comprehensive retention strategies that consider both intrinsic and extrinsic motivators.…”
Section: Introduction Importance Of Predicting Employee Turnovermentioning
confidence: 99%